ANALISIS KONTRASTIF FONEM VOKAL DAN KONSONAN BAHASA INDONESIA DENGAN BAHASA BENUAQ - Nurul Masfufah (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2018)
Linguistic characteristics in Indonesian and Benuaq language may be different and have their own characteristics, one of which is in their phonological aspects. This research aims to do a contrastive analysis of vowel and consonant phonemes in Indonesian and Benuaq language. It discusses about differences in vowel and consonant phonemes in Indonesian and Benuaq language. It uses structural linguistic theory to analyze the vowel and consonant phonemes based on phonological studies. It applies literature study method and interviews, like recording techniques and notes. The data analysis uses descriptive analytical methods to determine the differences in vowel and consonant phonemes. The results of this study reveal that Benuaq language has 23 consonant phonemes (b, p, pm, m, w, d, t, tn, s, n, l, r, j, c, ~ n, y, k, kG, g, G, q , h, and ?), six short vowels (i, u, e, |, o, and a), and five long vowels (i :, e :, u :, o :, and a :). Whereas, Indonesian has 22 consonant phonemes (b, p, f, m, w, d, t, s, ş, n, l, r, j, c, ~ n, y, k, kh , g, G, h, and z), six short vowels (i, u, e, |, o, and a), and no long vowels. Both languages have differences and similarities in the contrastive analysis.